2021
DOI: 10.1186/s13048-021-00793-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the survival outcomes of laparoscopy versus laparotomy in treatment of early-stage ovarian cancer: a systematic review and meta-analysis

Abstract: Background Laparoscopy has been widely used for patients with early-stage epithelial ovarian cancer (eEOC). However, there is limited evidence regarding whether survival outcomes of laparoscopy are equivalent to those of laparotomy among patients with eEOC. The result of survival outcomes of laparoscopy is still controversial. The aim of this meta-analysis is to analyze the survival outcomes of laparoscopy versus laparotomy in the treatment of eEOC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
3
9
0
1
Order By: Relevance
“…After RALS, similar overall, peri- and postoperative complication rates were found in comparison to conventional laparoscopic staging in all included cohort-studies (Table 2) [20–23,24 ▪ ]. RALS and conventional laparoscopic staging have similar EBL and LHS (Table 3) [16,17,19], as becomes clear in the studies of Nezhat et al [20] , Bellia et al [21] and Gallotta et al [22].…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…After RALS, similar overall, peri- and postoperative complication rates were found in comparison to conventional laparoscopic staging in all included cohort-studies (Table 2) [20–23,24 ▪ ]. RALS and conventional laparoscopic staging have similar EBL and LHS (Table 3) [16,17,19], as becomes clear in the studies of Nezhat et al [20] , Bellia et al [21] and Gallotta et al [22].…”
Section: Resultssupporting
confidence: 60%
“…There is no evidence that RALS is better than conventional laparoscopic staging. In general, numbers of retrieved lymph nodes do not depend on surgical approach [17,18,[20][21][22]24 & ], only one study shows a slightly larger number of lymph nodes harvested using RALS compared to conventional laparoscopic staging [23]. RR in MIS is not higher and in one study even lower compared to laparotomy, but follow-up is still short and insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the minimally invasive approach has been independently associated with tumor rupture (adjusted relative risk, 1.17; 95% CI: 1.06–1.29) [ 64 ]. In contrast, recent meta-analyses showed that: a) the upstaging and cyst rupture rates are comparable in MIS and laparotomy [ 66 ], b) the negative prognostic impact of iatrogenic tumor rupture is not proven [ 67 ], and c) neither the 3-year nor 5-year disease-free survival nor overall survival differs between patients undergoing MIS and those operated on by an open approach [ 67 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Laparotomija je tradicionalni kirurški pristup koji omogućava direktnu vizualizaciju organa putem velike incizije na abdomenu što podra zumijeva vrlo opsežnu kiruršku ozljedu. Laparosko pija, s druge strane, je minimalno invazivni kirurški pristup koji ima prednost u vidu smanjene veličine incizije, a time i niže učestalosti poslijeoperacijskih komplikacija i bržeg poslijeoperacijskog oporavka 2 . S napretkom endoskopske kirurgije, laparotomija se sve rjeđe koristi, ali je još uvijek primarni izbor u hitnoći i situacijama kad intraabdominalno stanje nije moguće zbrinuti drugom tehnikom 3 .…”
Section: Discussionunclassified